A feasible process for furfural production from the pre-hydrolysis liquor of corncob via biochar catalysts in a new biphasic system. (September 2016) - Deng, Aojie; Lin, Qixuan; Yan, Yuhuan; Li, Huiling; Ren, Junli; Liu, Chuanfu; Sun, Runcang
Graphical abstract: Highlights: A feasible process to produce furfural from the pre-hydrolysis liquor of corncob was developed. New biochar catalysts were prepared from corncob hydrolyzed residue. A new biphasic system (CPHL-NaCl/DMC) was proposed. The furfural yield of 81.14% with the selectivity of 83.0% was achieved. Abstract: A feasible approach was developed to produce furfural from the pre-hydrolysis liquor of corncob via biochar catalysts as the solid acid catalyst in a new biphasic system with dichloromethane (DCM) as the organic phase and the concentrated pre-hydrolysis liquor (CPHL) containing NaCl as the aqueous phase. The biochar catalyst possessing many acidity groups (SO3 H, COOH and phenolic OH groups) was prepared by the carbonization and sulfonation process of the corncob hydrolyzed residue. The influence of the catalytic condition on furfural yield and selectivity was comparatively studied. It was found that 81.14% furfural yield and 83.0% furfural selectivity were obtained from CPHL containing 5 wt% xylose using this biochar catalyst in the CPHL-NaCl/DCM biphasic system at 170 °C for 60 min. In addition, with the regeneration process, this catalyst displayed the high performance and excellent recyclability.